Botswana : Technical Assistance Report-Introducing a Medium-Term Expenditure Framework. (IMF Staff Country Reports; Country Report, 2014)
This Technical Assistance Report focuses on Botswana's Medium-term Expenditure Framework (MTEF). The Government of Botswana has committed to introduce the MTEF by 2016. The MTEF will provide a more explicit linkage between National Development Plan priorities and budget allocations by adopting a medium-term budgeting horizon. An MTEF model based on a binding nominal expenditure ceiling covering 100 percent of government expenditure is appropriate. To support the commitment to the resource allocations approved under the MTEF, a number of prioritization, control, and accountability arrangements need to be put in place.